Pro-ana versus Pro-recovery: A Content Analytic Comparison of Social Media Users’ Communication about Eating Disorders on Twitter and Tumblr - Branley, Dawn B.; Covey, Judith (Frontiers in Psychology, 2017)
Objectives: To compare how people communicate about eating disorders on two popular social media platforms – Twitter and Tumblr. Material and Methods: Thematic analysis was conducted to characterise the types of communications posted, and a content analysis was undertaken of between-platform differences. Results: Three types of content (pro-ana, anti-ana, pro-recovery) were posted on each platform. Overall, across both platforms, extreme pro-ana posts were in the minority compared to anti-ana and pro-recovery. Pro-ana posts (including ‘thinspiration’) were more common on Twitter than Tumblr, whereas anti-ana and pro-recovery posts were more common on Tumblr. Conclusions: The findings have implications for future research and health care relating to the treatment and prevention of eating disorders. Developers of future interventions targeting negative pro-ana content should remain aware of the need to avoid any detrimental impact on positive online support.